An Analisis Pedagogical Content Knowledge (PCK) Mahasiswa Pendidikan Guru SD terhadap Materi IPA melalui Instrument Content Representation (CoRe) dalam Konteks Pendidikan Kristen - Silalahi, Destya Waty; Silitonga, Bertha Natalina (Universitas Pelita Harapan, 2025)
Pedagogical Content Knowledge (PCK) is an essential competency for pre-service teachers, particularly science teachers at the elementary school level. PCK integrates content knowledge with pedagogical knowledge, enabling teachers to deliver science concepts effectively according to students’ cognitive development. In the context of Christian education, the understanding of science content and pedagogy should be grounded in a Biblical Christian Worldview (BCW) so that learning remains Christ-centered and founded on the truth of God’s Word. This study analysed the PCK of pre-service elementary school teachers in teaching science using the Content Representation (CoRe) instrument within a Christian education context. A descriptive quantitative method was employed with 78 student teachers as participants. The findings revealed that 29% of participants demonstrated PCK in the “very good” category, 62% in the “good” category, 8% in the “fair” category, and 1% in the “poor” category. These results emphasize the importance of equipping pre-service teachers with adequate PCK to strengthen the quality of science instruction, particularly when framed by a biblical worldview.